Design of Fermentation Machine With Work System Evaluation Using Fishbone Diagram Method in Surabaya MSMES - Cahyono Putra, Andhika; Saputro, Andre Ridho; Kusnanto, Hadi; Estiasih, Soffia Pudji; Adiaksa, Fitrah Thoriq (UNIPA PRESS, 2026)
Tempeh fermentation process in Micro, Small and Medium Enterprises (MSMEs) in Surabaya is generally still carried out conventionally, without the support of tools that are able to control the temperature and fermentation environment stably. Process inefficiencies and product quality irregularities are the main problems that business actors often face. This research aims to design a tempeh fermentation machine based on working system evaluation using the Fishbone Diagram method as an effort to develop appropriate technology. The research method used was descriptive-qualitative with an engineering approach, which included observation, interviews and field studies of three tempeh MSMEs in Surabaya. The results of the Fishbone Diagram analysis show that the main factors causing inefficiency include irregular work methods, lack of technical knowledge, lack of fermentation equipment, and unsupportive working environmental conditions. Based on the results of this evaluation, an MSME scale fermentation machine was designed with automatic temperature control, a capacity of 10–15 kg per batch, and an ergonomic design. Trials show that the machine is able to maintain a stable fermentation temperature, produce tempe products with more consistent quality, and reduce the physical workload of business actors. This research shows that the work systems approach in technology design is able to produce solutions that are contextual, functional and adaptive to the needs of MSMEs. These findings contribute to the development of science and technology in the fields of food technology, work ergonomics, and production equipment innovation based on local needs.